MODERN FURNITURE DESIGN TRENDS DESIGN STAGES (Neo Scientific Peer Reviewed Journal, 2024)
Brief information about the trend of modern furniture design is given, the functionality and requirements of the furniture are considered. Technical requirements for the furniture project, initial design solutions are defined.